2016
DOI: 10.1111/avj.12457
|View full text |Cite|
|
Sign up to set email alerts
|

Epidemiology and clinical presentation of canine distemper disease in dogs and ferrets in Australia, 2006–2014

Abstract: Continuation of vaccination against canine distemper virus is justified within Australia, particularly for younger dogs. Veterinarians should continue to consider distemper in their differential diagnosis of cases with neurological, gastrointestinal and respiratory presentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 28 publications
0
20
1
5
Order By: Relevance
“…Using surveillance and laboratory data, the authors report 48 cases of confirmed and suspected canine distemper virus (CDV) in dogs and ferrets across Australia, with an estimated mortality rate of 77% in dogs and 100% in ferrets, and cases concentrated in NSW and Victoria. Identified cases were also more common in summer months and occurred exclusively in young, unvaccinated dogs …”
Section: Small Animalsmentioning
confidence: 97%
“…Using surveillance and laboratory data, the authors report 48 cases of confirmed and suspected canine distemper virus (CDV) in dogs and ferrets across Australia, with an estimated mortality rate of 77% in dogs and 100% in ferrets, and cases concentrated in NSW and Victoria. Identified cases were also more common in summer months and occurred exclusively in young, unvaccinated dogs …”
Section: Small Animalsmentioning
confidence: 97%
“…A espécie mais acometida é a canina doméstica, porém o vírus pode infectar outras espécies canídeas selvagens, assim como os procionídeos e grandes felídeos (Zhang et al, 2017). Na Família Mustelidae os furões são altamente sucetíveis à infecção e mesmo uma carga viral baixa é letal para essa espécie (Vries et al, 2017;Wyllie et al, 2016). A infecção já foi relatada em outras espécies como em guaxinins, gambás, hienas e civetas (Rendon-Marin et al, 2019).…”
Section: Introductionunclassified
“…A cinomose acomete mais frequentemente cães em idades de 3 a 6 meses devido ao decréscimo dos anticorpos maternos neste período que favorecem o período de janela imunológica (Wyllie et al, 2016). Os animais infectados podem desenvolver inicialmente sinais clínicos sistêmicos que podem evoluir para sinais neurológicos (Sykes, 2013).…”
Section: Introductionunclassified
“…Existen investigaciones sobre la asociación entre el D. canino y la vacunación, en una se diagnosticó la enfermedad en perros vacunados y se atribuye a la introducción o circulación de cepas genéticamente diferentes que han mutado a través del paso de los años. Además de que la vacunación no otorga protección permanente, por lo que los animales deben ser vacunados periódicamente durante toda la vida (Greene & Appel, 2006;Gallo et al, 2007;Wyllie et al, 2016).…”
unclassified
“…Es la enfermedad multisistémica y letal más difundida globalmente en los cánidos y otras siete familias de mamíferos (Mustelidae, Procyonidae, Ursidae, Viverridae, Hyaenidae, Phocidae y Felidae), llegando a comprometer drásticamente la conservación de especies amenazadas debido a su altísima letalidad (Pardo et al 2005;Wyllie et al, 2016).…”
unclassified